The use of digital technologies in assessing the technical condition of historic structures - Bartosz Szostak; Michał Wac (Budownictwo i Architektura)
This article explores the use of modern digital technologies, such as 3D scanning and photogrammetry, in assessing the technical condition of historic structures. It compares traditional and digital inventory methods, emphasising the advantages of the latter in the precise and rapid acquisition of spatial data. Three types of laser scanning are described – simplified, handheld, and stationary – along with their applications in monument documentation. Case studies are presented where digital technologies were applied to the analysis and conservation of structures such as the ruins of Melsztyn Castle, Czersk Castle, the historic brickworks in Izbica, and the Juliusz Osterwa Theatre in Lublin. The findings demonstrate that these technologies enhance inventory accuracy, enable the detection of damage invisible to the naked eye, and save time and resources. Challenges related to processing large volumes of data and the need for specialised knowledge and standards are also discussed. In conclusion, the application of digital technologies in cultural heritage protection offers significant benefits and is invaluable for preserving monuments for future generations.